Indonesia’s Political Diplomacy in the Resolution of the Russia–Ukraine Conflict - Sholihin; Muhammad bin Abu Bakar; Zulhilmi (International Publisher (YAPENBI), 2025)
The armed conflict between Russia and Ukraine, which erupted in early 2022, has evolved into a global crisis—triggering food and energy shortages and threatening international geopolitical stability. This far-reaching turmoil has demanded diplomatic engagement from peace-committed nations, including Indonesia. This study aims to examine the role and strategies undertaken by the Indonesian government in responding to the conflict, as well as to uncover any underlying national interests behind its peace initiatives. Using a comprehensive literature review, the findings reveal that Indonesia positioned itself as a dialogue initiator and actively pursued bilateral and multilateral communications with the parties involved. While the diplomacy is officially framed as neutral and aligned with Indonesia’s constitutional mandate for peace, deeper analysis suggests pragmatic motives—such as safeguarding economic stability and bolstering Indonesia’s image as a credible global actor—also influence the peace mission.